The Animator's Body in Expanded Cinema. (November 2015) - Smith, Vicky
Building on phenomenological studies of the body and feminist structural materialist film theory and practice, this article proposes that performed methods of direct-on-film animation shape novel choreographies and produce original filmic patterns and rhythms. The author draws a parallel between Foucault's disobedient 'non-normative' body and non-standardized interventions with film technology. The article analyses the innovative choreographies that arise from rotoscoping techniques, direct-on-film practices and expanded cinema performances. Focusing specifically on Free Radicals (Len Lye, 1958) and Reel Time ( Annabel Nicolson, 1973), the author uses these analyses to shed light on her own performance of making films by moving in unusual ways, in time with technologies, and marking directly onto the film surface with the animated body. While engaging with structural materialist questions of film form, process and materials, this article departs from such modernist concerns to propose that the performance of filmmaking offers opportunities to explore the tenacity and vulnerability of particular bodies. The author suggests that performed filmmaking is equally about the traces of actions made on film and the unusual choreography that brings these marks into being.